Diversity, Equity, and Inclusion as Essential Tools in Promoting Teaching and Learning - Moses Adeleke Adeoye; Olaolu Paul Akinnubi; Musa Aremu Mahmud; Hassanat Abdullateef Jimoh (Indonesian Journal of Community and Special Needs Education, 2024)
This paper emphasizes the importance of diversity, equity, and inclusion (DEI) in creating a safe and welcoming environment and promoting social justice in education. DEI initiatives aim to create an environment that respects and values differences and that provides equal opportunities for all students to succeed. This paper provides an overview of the history of DEI in education, its importance, and positive outcomes for both students and educators. The paper also discusses the great benefits of promoting academic achievement by creating a more inclusive and welcoming learning environment that values and respects students' diverse backgrounds and experiences. The paper discusses the current state of promoting diversity, equity, and inclusion in teaching and learning and key strategies and best practices. This paper emphasizes the different forms that DEI initiatives can take and the importance of DEI for both students and educators.